CYP1A2 genotype modifies the effects of caffeine compared with placebo on muscle strength in competitive male athletes - Wong, O.; Marshall, K.; Sicova, M.; Guest, N. S.; García-Bailo, B.; El-Sohem, A. (International Journal of Sport Nutrition and Exercise Metabolism, 2021)
Caffeine is commonly used to improve athletic performance across a variety of sports. Previously, the CYP1A2 gene has been shown to modify the effects of caffeine on endurance performance. The effect of caffeine on strength and power activities is unclear and may differ depending on an individual`s CYP1A2 genotype. A randomized controlled trial was used to determine whether caffeine impacts strength and power, determined by the handgrip and vertical jump tests, respectively, and whether CYP1A2 genotype modifies any effects. Competitive male athletes (age = 25 ± 4 years) completed vertical jump (n = 97), and handgrip tests (n = 102) under three conditions: 0 (placebo), 2, or 4 mg of caffeine per kilogram of body mass (in milligrams per kilogram). CYP1A2 (rs762551) genotype was determined from saliva samples. No differences between caffeine doses and placebo were observed for strength or power; however, significant Caffeine × Gene interactions were observed for all exercise tests. Individuals with the CC genotype experienced a 12.8% decrease in handgrip strength with 4 mg/kg of caffeine compared with placebo (53 ± 11 kg vs. 61 ± 17 kg, p = .02). No differences were observed in those with the AC or AA genotypes. Despite observing a significant Caffeine × Gene interaction for vertical jump performance, no differences were observed between caffeine doses and placebo for all genotypes. In summary, caffeine (4 mg/kg) worsened handgrip strength performance in those with the CC genotype, but no differences were observed in those with the AC or AA genotypes. Athletes may want to consider their CYP1A2 genotype prior to using caffeine to improve muscle strength.